Example-based learning for vocational education: Adopted from Balinese heuristics learning - I Made Candiasa; Nyoman Santiyadnya; Nyoman Sukajaya; I Gede Partha Sindu (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
Vocational education has a very strategic role. Graduates produced are equipped with the competence to open new job opportunities or at least ready to enter the workforce. Therefore, vocational education development, such as training facilities, teacher development, and learning process improvement, must be intensified. This study tries to develop an example-based learning model for vocational education adopted from the learning model on cultural activities that surround Balinese people's daily life. A three-stage prototyping method was used: preliminary research, prototyping stage, and assessment stage. The syntax of example-based learning models consists of six phases: (1) conveying goals and motivating students, (2) organizing students into study groups and distributing worksheets, (3) guiding learning groups to do analogies, (4) drawing conclusions, (5) doing evaluation, and (6) giving awards. The social system that occurs is active students collaborate under the principle of democracy, while the teacher's role as a facilitator, counselor or consultant, and an adequate source of information becomes a support system. The learning model developed has been tested in small classes. The expert assessment provides content validity of 0.75 and the consistency coefficient of 0.78. The model's practicality from the teacher reaches 82% and 73% of students. During the trial, the new learning model's effectiveness reached 74%, while the efficiency was only 72%. These findings indicate that the learning model is feasible to be implemented with several recommendations, including the addition of a heuristic approach to work backward and create a hierarchy of similarity levels of examples and tasks in analogy.